The shariah viewpoint on the practice of underwriting and risk rating for individual participants in family Takaful - Htay, Sheila Nu Nu; Jawahir, Muhammad Khalid (2011)
The practice of underwriting and risk rating for individual participants in family takaful stems from the underwriting practice in life insurance, and thus could contain elements which contravene the essence of the shariah. A review of literature on takaful indicates that there are very few materials which look at the underwriting practice from a shariah perspective. The aim of this study was to find out the shariah viewpoint on the underwriting and risk rating practice for individual participants in family takaful. More specifically, it sought to gather the opinions of shariah scholars on the factors being used in the process of selection and classification of risks for individual participants to a family takaful pool. This study also explored the level of exposure and knowledge that shariah experts on takaful have pertaining to the underwriting practice. The study sample consisted of five purposefully selected shariah experts on takaful. The research method used was based on the Delphi technique and included two rounds of semi-structured face to face interviews with each participant. This study found that most of the shariah scholars interviewed did not seem to have a deep exposure to the underwriting and risk rating practice in family takaful. They however declared that underwriting and risk rating is permissible, although they had some concerns regarding some of the factors used in the underwriting process. The findings of this study will be of interest to the shariah scholars, takaful operators, regulatory bodies, academicians, and other stakeholders.